Comparative Study of Human Serum Paraoxonase-1 (PON-1) Activity in Type 2 Diabetes Mellitus: Insights into Oxidative Stress and Antioxidant Defence - Azeez, Reem M.; AL-Hashemi, Wisam Kadhum H.; Al-Auqbi, Tawfeeq F. R. (Iraqi Journal of Science, 2024)
Diabetes mellitus is a disease characterized by chronic high blood sugar levels resulting from defects in insulin secretion, insulin action, or both. Prolonged high blood glucose can increase production of reactive oxygen species, leading to elevated oxidative stress. The enzyme paraoxonase-1 (PON1), made in the liver and transported on high-density lipoprotein (HDL), acts as an antioxidant and can counter oxidative stress. This study aimed to compare PON1 activity between healthy controls, obese type 2 diabetics, and non-obese type 2 diabetics. There were 30 healthy controls, 30 obese type 2 diabetics (group I), and 30 non-obese type. Additionally, fasting lipid profiles, fasting plasma glucose, uric acid, albumin, and total bilirubin levels were determined using a clinical chemistry analyzer. The goal was to evaluate differences in PON1 activity as well as metabolic parameters between the three study groups. The results In comparison to the healthy control group, the diabetes group had Significantly higher blood sugar, serum cholesterol, serum triglycerides, serum LDL, and serum uric acid levels, Compared to the healthy control group, PON was Significantly lower in group II patients, Conclusion that Obese type 2 DM patients had significantly lower PON1 and HDL-C levels, which may indicate That the overweight has lessened biochemical functions for these substances. As dyslipidemia, insulin resistance, and high blood pressure are thought to be crucial factors in the cause of metabolic conditions in obese people, the reduced paraoxonase level may increase their likelihood of developing these conditions.